Photoporation-mediated spatial intracellular delivery of stem cell-derived cardiomyocytes - Laurens Léger; Chloë De Clercq; Jeffrey Aalders; Kiara Van Acker-Verberckt; Kevin Braeckmans; Jolanda van Hengel (MethodsX, 2024)
Human induced pluripotent stem cell-derived cardiomyocytes (iPSCCMs) are promising candidates for disease modeling and therapeutic purposes, however, non-viral intracellular delivery in these cells remains challenging. Gold nanoparticle (AuNP)-sensitized photoporation creates transient pores in the cell membrane by vapor nanobubble formation, allowing diffusion of extracellular biomolecules. This non-viral technique was employed to test and optimize its distinct physical mode of action in iPSCCMs. Photoporation optimization was aimed at achieving high delivery rates while minimizing cell death. Various AuNP concentrations, in conjunction with different laser fluences, were explored to facilitate the intracellular delivery of 10 kDa and 150 kDa FITC-labelled dextran as model macromolecules. Cardiomyocyte viability was assessed using the CellTiter-Glo® viability assay, while the delivery efficiency was quantified through flow cytometry. On 30 day-old cardiomyocytes, AuNP photoporation was able to yield ∼60 % delivery efficiency while maintaining a high cell viability (∼70 %). Overall, higher AuNP concentrations resulted in greater delivery efficiencies, albeit at the expense of lower cell viability. Finally, photoporation was capable of patterning a geometric shape, demonstrating its exceptional selective resolution in delivering molecules to spatially restricted regions of the cell culture. In conclusion, AuNP-photoporation exhibits considerable potential as an effective and gentle non-viral method for intracellular delivery in iPSCCMs. • AuNP-photoporation is a non-viral intracellular delivery method suitable for iPSCCMs with high efficiency and cell viability • This method is capable of spatially resolved intracellular delivery with excellent resolution